PEMBUATAN WEBSITE RESERVASI HOTEL BERBASIS PHP DAN MYSQL - ilham Syahrul Firmanysah; Marhaeni Marhaeni (JURNAL REKAYASA INFORMASI, 2019)
The hotel provides commercially available accommodation, provided for everyone to get services and lodging for eating and drinking. The purpose of making this application is to make it easier for customers to get / book hotels easily using the application and facilitate reception in making rooms, guests to be faster and better. Decision support system that can support prospective customers in determining hotel choices quickly, precisely and accurately. In this application, web-based system design, this application uses the PHP language with a MySQL database. Keyword : Hotel reservation, phpm mysql database